Adhesion between fiber post and root dentin: evaluation of post surface conditioning for bond strength improvement. - Amaral, M.; Rippe, M.; Konzen, M.; Valandro, L. (My University, 2011)
The aim of this paper was to evaluate two surface conditioning methods associated with the application of adhesive on the post surface for improving the bond to resin cement. Sixty single-rooted bovine teeth were sectioned at 16 mm in length, prepared (9 mm depth), embedded in a PVC cylinder using acrylic resin, and allocated into 3 groups (N.=20) according to post surface treatment: cleaning with ethanol (control group); etching with hydrogen peroxide; etching with hydrofluoric acid. Ten posts for each group were silanized and other 10 posts were silanized and received an adhesive agent. The posts were cemented with self-adhesive resin cement (RelyX U100 resin cement). All teeth were sectioned perpendicularly to the long axis (2 mm thickness per slice), submitted to push out bond strength testing and the type of failure was recorded. The obtained data were submitted to two-way ANOVA and Turkey's test, with the level of significance set at 5%. Neither the hydrofluoric acid or hydrogen peroxide post surface treatment, nor the adhesive application, had an influence on bond strength values. The main type of failure was adhesive between cement and dentin. Etching and the application of an adhesive on the post surface did not presented a significant influence on the bond strength results for the fiber post resin cement-root dentin assembly. The cement appears to adhere very well to the fiber post surface rather than the dentin surface.
Keywords: resin cement; animal; cattle; dental bonding; dental etching; dentin; evaluation; methodology; surface property; tooth crown; tooth root; Animals; Cattle; Dental Bonding; Dental Etching; Dentin; Post and Core Technique; Resin Cements; Surface Properties; Tooth Root